2022
DOI: 10.1002/cpe.6907
|View full text |Cite
|
Sign up to set email alerts
|

Ensemble learning of deep learning and traditional machine learning approaches for skin lesion segmentation and classification

Abstract: Melanoma is a type of a skin cancer or lesion which has the detrimental ramifications on the human health but with early diagnosis it can be cured easily. The actual identification of skin lesion is very challenging because of factors like a very minute difference between lesion and skin and it is very difficult to differentiate among skin cancer types due to visual comparability. Hence an autonomous system for the diagnosis of true skin cancer type is very useful. In this article, we took the leverage of ense… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…The challenging problem of skin lesion segmentation has also been solved by exploring ensemble approaches. Different ensemble-based approaches have been explored in the literature [ 15 ]. Deep learning and machine learning algorithms were used in an ensemble to classify skin lesions in this study.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The challenging problem of skin lesion segmentation has also been solved by exploring ensemble approaches. Different ensemble-based approaches have been explored in the literature [ 15 ]. Deep learning and machine learning algorithms were used in an ensemble to classify skin lesions in this study.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In some circumstances, deep learning approaches or conventional methods alone may not be superior to ensemble methods. For instance, a study [37], demonstrated that, for the segmentation of skin lesions, a combination of deep learning and conventional techniques produced superior results to either methodology used alone. Standard and deep learning methods will be used depending on the particular application.…”
Section: Implementing Lgbm For Segmentationmentioning
confidence: 99%